Trends in rheumatoid arthritis burden in China and globally, 1990–2021: A longitudinal study based on the GBD database - Zhengpeng Li; Hao Zeng; Bo Jin; Mianyu Zhang; Xiaoyun Zhang; Yuan Chai (PLoS ONE, 2025)
Background Rheumatoid arthritis (RA) is a chronic autoimmune disease that imposes significant health and economic burdens worldwide, particularly in developing countries such as China. Method In this study, the Global Burden of Disease, The GBD database system stratified the incidence,prevalence,death and disability-adjusted life years (DALYs) of RA in China and the world from 1990 to 2021 by age, sex and period. Joinpoint Regression Program 5.1.0 was then used to calculate average annual percent change (AAPC) and 95% confidence interval (95% confidence interval). CI) to identify trends in disease burden. In addition, data collation using WPS allows for the comparison of RA burdens across different age groups, genders and time points in China and globally, and the data is rigorously screened and processed to ensure accuracy and comparability. Results From 1990 to 2021, ASIR of RA in China increased by 0.54%, while the global ASIR rose by 0.41%.The number of RA cases in China increased cumulatively by 133%, compared to a global increase of 125.21%.Simultaneously, ASPR in China and globally increased by 17% and 14.44%, respectively.Regarding mortality, although the number of RA–related deaths increased in both China and globally, ASMR decreased by 26.23% in China and 22.86% globally.The trend in ASDR was consistent with ASMR, with declines of 0.40% in China and 1.46% globally.Furthermore, the study revealed significant gender disparities in RA both in China and globally, with women experiencing higher incidence, prevalence, mortality, and DALYs than men.The burden of RA increased significantly with age, particularly among middle–aged and older adults aged 45 and above. Conclusion Over the past 30 years, the burden of RA in China and globally has undergone significant changes.The study found that while RA related mortality and DALYs have slightly decreased in China and globally, the incidence and prevalence rates have continued to rise, particularly among women and middle–aged to elderly populations.Population aging and changes in lifestyle are key drivers of the increasing RA burden, with women showing higher susceptibility and burden due to their unique physiological characteristics and societal roles.The study highlights the need to strengthen early screening and intervention, optimize personalized treatment plans, and pay special attention to the unique needs of elderly and female populations.Additionally, promoting healthy lifestyles, improving primary healthcare services, and implementing supportive policies can effectively alleviate the health and socioeconomic burden of RA, ensuring a better quality of life for patients.